KEBIJAKAN PERTAHANAN AUSTRALIA DAN RESPONS NEGARA-NEGARA ASIA TIMUR DAN SELANDIA BARU - Alami, Athiqah Nur (Jurnal Penelitian Politik, 2006)
Australia’s position in Asia Pacific has a significant consideration on their policy making, primarily defense policy. Their close relationship with The United States of America and the United Kingdom sometimes becomes impediment in building relations with neighbor countries in Asia. The Australia 's defense policy more or less reflects the big countries 'interest in Asia Pacific, including Proliferation Security Initiatives, SM-3 andAMIZ policies. Those policies bring about various reactions from the East Asian Countries and New Zealand. The different reactions are related strongly with their interest and cooperation with Australia.